Effects of the vibrating capsule on colonic circadian rhythm and bowel symptoms in chronic idiopathic constipation. Issue 11 (25th May 2020) - Rao, Satish S. C.; Lembo, Anthony; Chey, William D.; Friedenberg, Keith; Quigley, Eamonn M. M.
Abstract: Background: Constipated patients remain dissatisfied with current treatments suggesting a need for alternative therapies. Aim: Evaluate the mechanistic effects of oral vibrating capsule in chronic idiopathic constipation (CIC) by examining the temporal relationships between the onset of vibrations, complete spontaneous bowel movements (CSBM), and circadian rhythm. Methods: In post hoc analyses of two double‐blind studies, CIC patients (Rome III) were randomized to receive 5 active or sham capsules/week for 8 weeks. The capsules were programmed for single vibration (study 1) or two vibration sessions with two modes, 8 hours apart (study 2). Daily electronic diaries assessed stool habit and percentage of CSBMs associated with vibrations. Responders were patients with ≥ 1 CSBM per week over baseline. Results: 250 patients were enrolled (active = 133, sham = 117). During and within 3 hours of vibration, there were significantly more % CSBMs in the active vs. sham group (50% vs. 42%; P  = .0018). In study 2, there were two CSBM peaks associated with vibration sessions. Significantly more % CSBMs occurred in active mode 1 (21.5%) vs. sham (11.5%); ( P  = .0357). Responder rates did not differ in study 1 (active vs. sham: 26.9% vs. 35.9%, P  = .19) or study 2 (mode 1 vs. sham: 50% vs. 31.8%, P  = .24; mode 2 vs. sham: 38.1% vs. 31.8%, P  = .75). Device was well‐tolerated barring mild vibration sensation. Conclusions: Vibrating capsule may increase CSBMs possibly by enhancing the physiologic effects of waking and meals, and augmenting circadian rhythm, although responder rate was not different from sham. Two vibration sessions were associated with more CSBMs.